0253 The Association Between Sleep Health and Mood in Sedentary Desk Workers. (25th May 2022) - Vogan, Olivia; Cheruka, Caitlin; Egeler, Mara; Kubala, Andrew; Sanders, Rachel; Paley, Joshua; Patel, Sanjay; Hall, Martica; Perera, Subashan; Jakicic, John; Gibbs, Bethany; Kline, Christopher
Abstract: Introduction: Poor sleep, most commonly insufficient sleep duration or low sleep quality, has been linked with disruptions of mood. However, it is unclear how sleep health—more broadly, other multiple dimensions of sleep—is associated with mood. The purpose of this study was to investigate the associations between sleep health and mood in a sample of desk-working sedentary adults. Methods: This cross-sectional study used baseline data from inactive adults with desk-based jobs (N=125, 49.6% female, 43.9±10.6 years) who enrolled in an ongoing clinical trial. Sleep was assessed using validated questionnaires and 7 nights of actigraphy. Collectively, these measures were utilized to assess six different sleep dimensions: regularity, satisfaction, alertness, timing, efficiency, duration. Each dimension was categorized as "good" or "poor". A sleep health score was calculated by summing the number of good dimensions (range: 0-6; higher is better). Mood was assessed using Profile of Mood States (POMS); its 7 subscales (tension, anger, fatigue, depression, esteem-affect, vigor, confusion) were summed (with a constant of 100) to create a Total Mood Disturbance (TMD) score. Multiple linear regression models examined associations between sleep health and mood adjusting for age, gender, and whether pre- or post-COVID-19. Results: The mean sleep health score was 4.7±1.1; the mean TMD score was 96.6±18.5. Better sleep health was associated with lesser TMD (β=-0.32, p<0.001) and better mood on each of the POMS subscales (β≥0.18, p<0.05), aside from esteem-related affect (p=0.31). Of the individual sleep dimensions, only satisfaction, alertness, and efficiency were associated with TMD (β≥0.18, p<0.05). Satisfaction was the only individual sleep dimension that was consistently associated with better mood on each subscale (β≥0.17). Alertness, efficiency, and duration were inconsistently associated with individual mood subscales. Regularity and timing were not associated with any mood subscales (p≥0.267 and p≥0.073, respectively). Conclusion: Better sleep health was associated with less TMD. Satisfaction was the sleep dimension that consistently associated with each subscale of mood. The cross-sectional, observational design limits casual inference between sleep health and mood disturbance due to a lack of temporality and the potential for residual confounding. Support (If Any): This study was funded by National Institutes of Health (NIH) grants R01HL134809 and R01HL147610.